2004
DOI: 10.4049/jimmunol.172.11.6528
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Hemokinin Has Substance P-Like Function and Expression in Inflammation

Abstract: Substance P (SP) belongs to the tachykinin family of molecules. SP, cleaved from preprotachykinin A, is a neuropeptide and a proinflammatory leukocyte product. SP engages neurokinin 1 receptor (NK-1R) to stimulate cells. Hemokinin (HK) is another tachykinin that binds NK-1R. HK comes from preprotachykinin C, which is distinct from preprotachykinin A. We determined whether HK functions like SP at inflammatory sites. Preprotachykinin C mRNA was in murine schistosome granulomas and intestinal lamina propria monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 30 publications
3
38
0
1
Order By: Relevance
“…Consistent with this notion, we were able to detect NK-1 but not NK-2 or NK-3 mRNA in B cells (data not shown). Like in many other assays (21,23,25,26,42,43), HK-1 activity on B cells could be fully reproduced with SP, which is in accord with several earlier reports documenting enhanced Ig secretion in the presence of SP (44). Given the apparent functional overlap, an important issue is the tissue distribution of the two peptides.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with this notion, we were able to detect NK-1 but not NK-2 or NK-3 mRNA in B cells (data not shown). Like in many other assays (21,23,25,26,42,43), HK-1 activity on B cells could be fully reproduced with SP, which is in accord with several earlier reports documenting enhanced Ig secretion in the presence of SP (44). Given the apparent functional overlap, an important issue is the tissue distribution of the two peptides.…”
Section: Discussionsupporting
confidence: 77%
“…As the first tachykinin peptide primarily expressed in non-neuronal tissues, the immunoregulatory function of HK-1 is of considerable interest. In T cells, HK-1 was found to enhance IFN-g production after Ag stimulation with equal potency to SP (42). More recently, Janelsins and colleagues demonstrated that both HK-1 and SP rescued bone marrow-derived dendritic cells (DCs) from apoptosis induced by the deprivation of growth factors, probably by activating the PI3K-Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another of the most regulated genes was tac4a, which encodes a family of species-divergent neurotransmitters called tachykinins (Page 2004(Page , 2006. Although the exact function of tac4 paralogs in zebrafish has not been unveiled, hemokinin 1 (Hk1), a product of the Tac4 gene, is reported to be expressed along with substance P at sites of chronic inflammation in mice (Metwali et al 2004), a typical NAFLD feature. It is well documented that the chronic inflammation caused by metabolic syndrome is one of the main causes of NAFLD evolution into NASH, which can eventually cause liver fibrosis, a process characterized by the deposition of new collagen and matrix molecules in the extracellular space.…”
Section: Model Characterizationmentioning
confidence: 99%
“…Like SP, HK-1 can be expressed at sites of inflammation. It is produced by T cells and macrophages at least in the granulomas of murine schistosomiasis and in the gut (18). We showed that neither IL-12 nor IL-23 induces its expression in isolated splenic or LP T cells or macrophages cultured in vitro.…”
Section: Discussionmentioning
confidence: 84%